Diets and dieting : a cultural encyclopedia - Gilman, Sander L. (Routledge, 2008)
From the Publisher: Diets and dieting have concerned-and sometimes obsessed-human societies for centuries. The dieters' regime is about many things, among them the control of weight and the body, the politics of beauty, discipline and even self-harm, personal and societal demands for improved health, spiritual harmony with the universe, and ethical codes of existence. In this innovative reference work that spans many periods and cultures, the acclaimed cultural and medical historian Sander Gilman lays out the history of diets and dieting in a fascinating series of articles.